Bilateral congenital semicircular canal malformation and hearing loss - case report - Costa, Joana Raquel (2020)
The main aims of this observational study were to describe a poorly characterized malformation of the inner ear termed bilateral congenital semicircular canal malformation; determine if the degree and pattern of semicircular canal dysmorphology and the presence or absence of a well-formed cochlea predict audiological outcomes, type, and severity of congenital hearing loss; and investigate its relationship with known syndromic forms of hearing loss. Review of eight cases of hearing loss with radiographic evidence of congenital semicircular canal malformation was performed. Information was collected on clinical history, physical examination, computed tomography study and serial audiograms for all patients. Analyzed features included other syndrome-characteristic phenotypic dysmorphologies, audiometric configuration, severity and type of hearing loss, type of audiological rehabilitation, and presence of associated inner ear abnormalities besides those in the vestibular system. Among the eight cases included in the study, six patients had recognized syndromes/chromosomal abnormalities. Hearing loss was moderate to profound in all cases. All patients had bilateral semicircular canal deformities, with usually identical anatomical pattern on each side. Of the eight cases, six had normal cochlear development; malformations in the tympanic membrane and external auditory canal were only found in one; changes in ossicular chain were found in three patients; vestibules and vestibular aqueduct were normal in most cases; and abnormalities of oval window development and hypoplasia were found in two cases. The present study shows that a correlation between the severity and type of hearing loss and radiographic abnormalities is difficult to establish. Hearing loss associated with semicircular canal dysplasia is more likely due to anomalous membranous labyrinth development, which is not radiologically detectable by computerized tomography scan.